The Detoxification Effects of Melatonin on Aflatoxin-Caused Toxic Effects and Underlying Molecular Mechanisms - Chongshan Dai; Daowen Li; Tony Velkov; Jianzhong Shen; Zhihui Hao (Antioxidants)
Aflatoxins (AFTs) are a form of mycotoxins mainly produced by Aspergillus flavus and Aspergillus parasiticus, which are common contaminants in various agricultural sources such as feed, milk, food, and grain crops. Aflatoxin B1 (AFB1) is the most toxic one among all AFTs. AFB1 undergoes bioactivation into AFB1-8,9-epoxide, then leads to diverse harmful effects such as neurotoxicity, carcinogenicity, hepatotoxicity, reproductive toxicity, nephrotoxicity, and immunotoxicity, with specific molecular mechanisms varying in different pathologies. The detoxification of AFB1 is of great importance for safeguarding the health of animals and humans and has increasingly attracted global attention. Recent research has shown that melatonin supplementation can effectively mitigate AFB1-induced multiple toxic effects. The protection mechanisms of melatonin involve the inhibition of oxidative stress, the upregulation of antioxidant enzyme activity, the reduction of mitochondrial dysfunction, the inactivation of the mitochondrial apoptotic pathway, the blockade of inflammatory responses, and the attenuation of cytochrome P450 enzymes’ expression and activities. In summary, this review sheds new light on the potential role of melatonin as a potential detoxifying agent against AFB1. Further exploration of the precise molecular mechanisms and clinical efficacy of this promising treatment is urgently needed.